The contribution of youth sport football to weekend physical activity for males aged 9 to 16 years: Variability related to age and playing position - Fenton, S. A. M.; Duda, J. L.; Barrett, T. (Pediatric Exercise Science, 2015)
The aims of this study were (1) to determine minutes of moderate-to-vigorous physical activity (PA) and vigorous PA accrued in youth sport football (also internationally referred to as soccer), and the contribution toward daily weekend moderate-to-vigorous PA and vigorous PA for males aged 9-16 years, and (2) to investigate variability in these outcomes related to age and playing position. One hundred and nine male grassroots footballers (Mean age = 11.98 ± 1.75 years) wore a GT3× accelerometer for 7 days. Weekend youth sport football participation and playing position were recorded. Youth sport football moderate-to-vigorous PA (M = 51.51 ± 17.99) and vigorous PA (M = 27.78 ± 14.55) contributed 60.27% and 70.68% toward daily weekend moderate-to-vigorous PA and vigorous PA, respectively. Overall, 36.70% of participants accumulated =60 min moderate-to-vigorous PA and 69.70% accrued = 20 min of vigorous PA during youth sport. For participants aged 13 to16 years, youth sport football moderate-to-vigorous PA and vigorous PA were significantly higher, and contributed a greater amount toward daily weekend moderate-to-vigorous PA and vigorous PA than for participants aged 9-12 years (p = <.01). Youth sport football is an important source of moderate-to-vigorous PA and vigorous PA at the weekend for male youth, and particularly for adolescents. Participation may offer opportunity for weekend engagement in vigorous PA toward health enhancing levels